THE INFLUENCE OF TAXPAYER AWARENESS, TAX SANCTIONS, AND THE IMPLEMENTATION OF THE E-FILLING SYSTEM ON TAXPAYER COMPLIANCE IN MICRO, SMALL, AND MEDIUM ENTERPRISES - Tanady, Annabelle Kael; Lukman, Hendro (International Journal of Application on Economics and Business, 2024)
The objective of this research is to examine the influence of taxpayer awareness, tax sanction, and the implementation of the e-filling system on taxpayer compliance in micro, small and medium Enterprises (MSMEs). The population is all MSMEs taxpayers in DKI Jakarta. The sample was 160 MSMEs taxpayers in DKI Jakarta. The sample selection technique in this research used a questionnaire media which was then distributed using Google Form media and used a convenience sampling method sampling technique. Data was obtained using the multiple linear regression analysis method on SmartPLS 4 Software. The results of this study show that taxpayer awareness has no influence on MSMEs taxpayer compliance, whereas through tax sanctions and the implementation of the E-Filling system it could influence MSMEs taxpayer compliance.